Clinical and prognostic significance of OPN and VEGF expression in patients with non-small-cell lung cancer. Issue 4 (August 2015) - Lin, Qunying; Guo, Lijing; Lin, Guosheng; Chen, Zhiwei; Chen, Tonghuan; Lin, Juan; Zhang, Bo; Gu, Xiaobin
Highlights: This was the first study investigating OPN and VEGF expression in NSCLC including patients with all stages (I–IV). The present study showed the clinical significance of OPN and VEGF expression in NSCLC. NSCLC Patients with OPN(+)/VEGF(+) had the worst prognosis among groups. OPN expression and VEGF expression were independent prognostic factors for NSCLC. Abstract: Background: Osteopontin (OPN) and vascular endothelial growth factor (VEGF) play important roles in cancer progression and angiogenesis. In the current study we aimed to investigate the clinical significance of OPN and VEGF expression in patients with non-small-cell lung cancer (NSCLC) and to investigate their prognostic value for NSCLC. Methods: Immunohistochemical staining was used to detect the expression of OPN and VEGF in 146 NSCLC patients undergoing surgical resection in our hospital between 2006 and 2008. The associations between OPN and VEGF expression and clinicopathological data were analyzed using chi-square test analysis. Survival analysis was performed using the Kaplan–Meier method. The prognostic values of OPN and VEGF were evaluated by univariate and multivariate Cox proportional hazard model analysis. Results: OPN and VEGF expression was positive in 94 and 86 out of 146 NSCLC specimens, respectively. OPN expression was significantly associated with gender ( P  = 0.002), TNM stage ( P  < 0.001) and tumor differentiation ( P  = 0.008). VEGF expression was significantly associated with TNM stage ( P  = 0.015), tumor differentiation ( P  = 0.032) and lymph-node status ( P  < 0.001). There was a significant correlation between OPN and VEGF expression ( P  = 0.035). Survival analysis indicated that OPN(+)/VEGF(+) patients had the worst prognosis. Furthermore, univariate and multivariate analysis suggested that tumor stage, lymph-node metastases, OPN expression and VEGF expression were independent prognostic factors for NSCLC. Conclusion: The data suggest that OPN and VEGF expressions could serve as prognostic factors for NSCLC.